Review Literatur Pengujian Empiris Model Pembentukan Portofolio Optimal “Mean-Variance Markowitz” - Dewi Indriasih; Abdulloh Mubarok; Eva Anggra Yunita; Aminul Fajri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The article aims to review the literature on the results of empirical testing of the model of mean-variant (M-V) Markowitz optimal portfolio determination. Through the literature review method, the study obtained 17 empirical research articles with various findings. Several test results support and strengthen model of M-V Markowitz in determining the optimal portfolio. The Others do not support the application of the M-V Markowitz Model. Other researchers tried to propose an adjustment model and then tested the model. The results of the testing found that the adjusted model of M-V Markowitz was better at determining the optimal portfolio compared to the initial model.